2020
DOI: 10.1038/s41467-020-18821-x
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide chromatin accessibility is restricted by ANP32E

Abstract: Genome-wide chromatin state underlies gene expression potential and cellular function. Epigenetic features and nucleosome positioning contribute to the accessibility of DNA, but widespread regulators of chromatin state are largely unknown. Our study investigates how coordination of ANP32E and H2A.Z contributes to genome-wide chromatin state in mouse fibroblasts. We define H2A.Z as a universal chromatin accessibility factor, and demonstrate that ANP32E antagonizes H2A.Z accumulation to restrict chromatin access… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 75 publications
(128 reference statements)
3
20
0
Order By: Relevance
“…As H2A.Z is incorporated into the same regions of the endogenous H2A.Z in the RhIP assay, the pre-incorporated H2A.Z in the chromatin may be dynamically exchanged with the exogenously added H2A.Z in the RhIP assay. The exchange reaction requires the H2A.Z-H2B complex to be evicted from nucleosomes, and ANP32E has this eviction activity ( Gursoy-Yuzugullu et al, 2015 ; Murphy et al, 2020 ; Murphy et al, 2018 ; Obri et al, 2014 ). We then examined whether ANP32E is involved in the deposition of H2A.Z in the RhIP assay.…”
Section: Resultsmentioning
confidence: 99%
“…As H2A.Z is incorporated into the same regions of the endogenous H2A.Z in the RhIP assay, the pre-incorporated H2A.Z in the chromatin may be dynamically exchanged with the exogenously added H2A.Z in the RhIP assay. The exchange reaction requires the H2A.Z-H2B complex to be evicted from nucleosomes, and ANP32E has this eviction activity ( Gursoy-Yuzugullu et al, 2015 ; Murphy et al, 2020 ; Murphy et al, 2018 ; Obri et al, 2014 ). We then examined whether ANP32E is involved in the deposition of H2A.Z in the RhIP assay.…”
Section: Resultsmentioning
confidence: 99%
“…H2A.Z accumulates at estrogen response elements that are bound by FOXA1 and loss of H2A.Z impairs both FOXA1 binding and polymerase recruitment. ANP32E is a chromatin chaperone that regulates the genomic localization of H2A.Z to control locus-specific chromatin state dynamics [ 14 ]. In recent work, we showed that ANP32E antagonizes H2A.Z installation, such that ANP32E loss causes a global increased H2A.Z enrichment, heightened chromatin accessibility and amplified transcription factor binding at open sites, in cultured mouse fibroblasts [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…ANP32E is a chromatin chaperone that regulates the genomic localization of H2A.Z to control locus-specific chromatin state dynamics [ 14 ]. In recent work, we showed that ANP32E antagonizes H2A.Z installation, such that ANP32E loss causes a global increased H2A.Z enrichment, heightened chromatin accessibility and amplified transcription factor binding at open sites, in cultured mouse fibroblasts [ 14 ]. ANP32E may function similarly in breast tumors, influencing the binding of key oncogenic transcription factors, such as FOXA1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations